(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
This study investigated the effect of blended learning approach on students’ academic achievement in Mathematics in Delta north senatorial district of Delta state. Three research questions and hypotheses were each raised to guide the study. The scope of the study covered the effect of blended learning approach on students’ academic achievement in SSS2 Mathematics in Algebra and Probability. The study is delimited to public secondary schools in the senatorial district. The design of the study was a quasi experimental design of pretest-posttest control group. The population of the study comprised all Senior Secondary School 2 (SSS 2) students in public secondary schools in the nine local government areas of Delta north senatorial district in the 2024/2025 academic session. The population of the study was 3,473 candidates. A multi stage sampling technique was used to draw a sample size of 225 SSS2 Mathematics students (105 males, and 120 females). Mathematics Achievement Test (MAT) was used for data collection. The reliability of the instrument was 0.79 obtained using Kudar-Richardson formulae 20 (KR-20). Analysis of Covariance (ANCOVA) and independent sample t-test were employed to test the hypotheses at a 0.05 level of significance. The findings of the result revealed that students exposed to the blended learning approach performed better than those exposed to the conventional lecture method. The findings also showed a significant difference between male and female students exposed to blended learning approach in favor of male students, and no interaction effect between instructional methods and sex. Based on the findings of this study, blended learning approach should be practiced thoroughly by Mathematics teachers as the method has been proven effective in enhancing students’ Mathematics academic achievement.